Hijazi line Damascus - Medina Railway (historical study) (Journal of the College of Basic Education, 2022)
The reforms, including the Urban in the Ottoman Empire of the most important achievements by some Ottoman sultans, but such a strategic project (Railway Damascus - Medina) carried out by the Sultan Abdul Hamid II, was a landmark in its significance the political and economic leaving fingerprints in the psyche Sultan Abdul Hamid and who stood with him in the completion of a project like this, some of the some of the colonial powers, including Britain, which was hindering and foil these projects so it was optional for this study because they carry a lot of goals and meanings charity to link sons one state to each other, especially the political goals and economic, and it was such a real dream projects have been accomplished during the reign of Sultan Abdul Hamid